Law and literature in comparative perspectives: Tracing Shylock's case from Italian novelle to American courtrooms. (August 2019) - Apolloni, Jessica
Recent work on law's connection to literature has shown the immense overlap in narrative structuring, power dynamics, and social prejudices inherent to both literary and legal texts. Yet law-literature studies have often relied on nationalistic boundaries, overlooking the intense interchange of legal and literary ideas circulating across spatial and temporal divides. This article studies Italian novelle from a comparative perspective to uncover how concepts of law, justice, and authority circulate in literary texts across diverse geographies and legal systems. I specifically trace Shylock's case, from its origins in the Italian novelle genre to the utilizations of The Merchant of Venice in American legal training and courtrooms. This case study illustrates the power of literature to synthesize diverse legal environments, influence popular understandings of law, and provide a comparative perspective of justice to both legal scholars and public audiences.